Contribuições da teoria das inteligências múltiplas aos estudos da dislexia - Lanfredi, Caila (2013)
This study was developed in the research line Educational Processes and Language, whose research topic to discuss the contributions of the Theory of Multiple Intelligences to Dyslexia studies investigating the difficulty of the language related to reading and writing. The theoretical study was based on the theory of Howard Gardner, in the case of a cognitive psychologist and educational state-unidense. This scholar questions the current cognitive theories, bringing a different view of incisive intelligence and human potential guided in different domains. This text can be considered qualitative investigative, using literature to understand the processes involved in learning. For the viability of this dissertation was necessary to study the history of dyslexia to reach the contemporary, making thus a resumption of historical thought and what they think about dyslexia, aiming to understand how dyslexics were seen in the past and are seen in the present and, above all, sought to subsidies that allow working with greater accuracy dyslexia , presenting studies of Gardner, in order to investigate what his theory of Multiple Intelligences can help dyslexics find other skills that furthers shortcomings own dyslexia, bringing to light new perspectives and multidisciplinary looks. In the first chapter addressed the Theory of Multiple Intelligences Howard Gardner guided the thesis. In the second chapter, concerned to analyze theoretically the difficulty in focus: Dyslexia, based on studies of Sally Shaywitz, Giselle Massi, Margaret Snowling and Michael Abram Farreal Topczewski. In the last chapter, held the closing text of this dissertation, raising some questions related to Dyslexia, pointing out new perspectives to teaching and learning, guided by a new vision of human potential and intelligence